The Paradigm of Cosmovision – Based Conservation - Agung, Anak Agung Gde; Suprina, Rina; Pusparini, Marissa (TRJ Tourism Research Journal; Vol 3 No 2 (2019): (TRJ) Tourism Research Journal, 2019)
The purpose of this article is to try to explain the benefits that can be obtained by learning the traditional knowledge of indigenous people around the world to overcome current perceptions and practices about the environment that has experienced serious degradation. Traditional Ecological Knowledge offers the appropriate tools to learn more  the insights of “Sacred Balance”. The research method used in this article was an in-depth analysis of the literature written by experts in the fields of biodiversity, culture, anthropology and ethnography. Synthesis has been taken from the review of this literature as described in this article with various modifications from field verification. This verification has been carried out in Bali through panel discussions with the heads and members of the banjar (village association) in Gianyar, Jatiluwih, Kerobokan and Ubud. The panel's focus was on the concept and practice of "Tri Hita Karana", the philosophy of Balinese life that embodies the cosmovision of "Sacred Balance". The results showed that the cosmovision of "Sacred Balance" which emphasizes on harmony and equilibrium as a way of life is a philosophy that can be emulated by humans throughout the world not only to achieve conservation but also a means for peace and happiness. This can be obtained by further studying this philosophy which has been practiced since time long standing by many people around the world through deeper studies of Traditional Ecological Knowledge.